1997
DOI: 10.2307/3433608
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Outdoor Fungal Spore Concentrations on Daily Asthma Severity

Abstract: The relationship between day-to-dy changes The present study was designed to investigate the potential interactive and independent effects of ozone (03) and outdoor aeroallergens (pollens and molds) on daily asthma severity. This was carried out using the panel study design, which is characterized by longitudinal analyses of daily data for a panel of asthmatics, with each subject acting as his or her own control. This study was conducted in the small Southern California community of Alpine, California, over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…[5][6][7] There may be several reasons for this lack of consistency. It may result from geographical differences in the allergen levels, 5 in the prevalence of atopy and bronchial responsiveness, 12 and in the clinical and pathological nature of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] There may be several reasons for this lack of consistency. It may result from geographical differences in the allergen levels, 5 in the prevalence of atopy and bronchial responsiveness, 12 and in the clinical and pathological nature of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have addressed the potential for a confounding role by pollen and spores and have consistently found a lack of confounding effect on the association between air pollution and asthma admissions 1 7 or symptoms. [8][9][10][11][12] Pollen has rarely been associated with asthma symptoms, 13 while spore counts have consistently been found to affect the symptoms of asthma. 9-12 14 Experimentally, there is firm support for the hypothesis that O 3 , NO 2 , SO 2 , and particles modulate allergic responses in asthmatic subjects, 15 which has been observed for O 3 16-18 and NO 2 in human volunteers.…”
mentioning
confidence: 99%
“…9-12 14 Experimentally, there is firm support for the hypothesis that O 3 , NO 2 , SO 2 , and particles modulate allergic responses in asthmatic subjects, 15 which has been observed for O 3 16-18 and NO 2 in human volunteers. [18][19][20][21][22] However, only a few studies in real air have analysed the synergism between air pollutants and pollen 1 and fungal spores [9][10][11][12] in exacerbations of asthma.…”
mentioning
confidence: 99%
“…Some studies have found an association with total counts of mould spores,11 14 16 whereas others have reported a correlation between severity indices and specific groups or species, including basidiospores14-16; Cladosporium 13; Alternaria 16; and Didymella exitialis. 12 The release of spores of Didymella and Sporobolomyces in response to rapid changes in humidity was suggested as a possible explanation for an outbreak of asthma attacks after a thunderstorm around Birmingham, United Kingdom, in July 1983 17.…”
mentioning
confidence: 99%